Large Parks - Czerniak, Julia; Hargreaves, George (New York: Princeton Architectural Press, 2007)
Large Parks examines an increasingly hard to define landscape type: the urban park. By viewing such landscapes through the lens of size, the essays contained here cut across conventional binary categories of classification - historic or contemporary, built or unbuilt, competition - sponsored or commissiones - and enable us to analyze landscapes not usually considered collectively. From a discussion of historic parks such as New York's Central Park and Paris's Bois de Boulogne, to intriguing new projects such as the Orange Country Great Park in California, Large Parks highlights the intricacies that go into designing these massive and culturally significant works. By analyzing design, concepto, construction, and technique, Large Parks gives designers concrete insight into the complicated task of designing large park that is structured enough to give form, identity, and meaning to the site, but pliant enough to adapt to changing ecologies, demands, and uses.
Speculating on size -- Sustainable Large Parks: ecological design or designer ecology? -- Uncertain parks: disturbed sites, citizens, and risk society -- Matrix landscape: construction of identity in the large park -- Large parks: a designer's perspective -- Re-placing process -- Conflict and erosion: the contemporary public life of large parks -- Legibility and resilience.
Keywords: Arquitectura del Paisaje; Parques Urbanos; Espacios Públicos